Tlingit totem pole, houseposts, and canoe, Sitka, Alaska, June 1906. - Cobb, John N.
Note from Cobb field notebook: Totem poles, Sitka, Alaska. This group has been at Sitka for a long time. Note from unidentified source: Pole from Old Kasaan, four houseposts from Sonxet, carved canoe. Same as NA2708.